The deviant security practices of cyber crime - Sandt, Erik H. A. van de (Brill Nijhoff, 2021)
In this book academic and police officer Erik van de Sandt researches the security practices of cyber criminals. While their protective practices are not necessarily deemed criminal by law, the countermeasures of cyber criminals frequently deviate from prescribed bona fide cyber security standards. This book is the first to present a full picture on these deviant security practices, based on unique access to confidential police sources related to some of the world's most serious and organized cyber criminals. The findings of this socio-technical-legal research prove that deviant security is an academic field of study on its own, and will help a non-technical audience to understand cyber security and the challenges of investigating cyber crime